Sustentabilidade e usos múltiplos da água da Barragem Poção da Ribeira-SE - Mendonça, Nivaldo dos Santos (2013)
Water is a natural resource essential to the maintenance of different life forms, as is in the processes of evolution and co-evolution. However, their distribution in quantity occurs irregularly along the earth, and their quality standards are variable and deriving the uses to which water resources are submitted. Recognizing the importance of water and its quantitative and qualitative availability in a fountain in front of their multiple uses is that the present work has as objectives: quantify the main direct uses of the waters of the dam Poção da Ribeira; characterize the main indirect uses and its users, check for possible conflicts over water use and generate sustainability index based on indicators: social, economic and environmental use of waters of said dam. In seeking to achieve these objectives, visits were made to government agencies (Deso, Cohidro, Public Prosecution Service, Police, Departments of Education, Health and Public Works), water samples were collected and analyzed; were interviewed: irrigators, the association s president of fish farmers and owners of bars on the shores of the dam Poção da Ribeira, besides, have been held the water balance of the reservoir. The water from the dam have as major uses consultative: the distribution of water for human consumption and use in irrigation, these are not conflicting uses in quantitative terms, even when water intended, to the lots, for irrigation, are also used by irrigators for other purposes. Among the indirect uses of waters from the dam are highlighted use for recreation, fishing and pisciculture, and it was found the existence of a conflict, which is not manifest, between aquaculture and traditional fisheries. Irregularities were also observed, from the viewpoint of the law with respect to shapes occupying the edges of the reservoir and waste disposal to the barrier and its main affluent. Among the eleven indicators used in making the sustainability index, it was found that indicators: Ratio between the amount of applied water the amount of water resources needed to satisfy the needs of cultivated plants; Percentage of police incidents in the area of irrigated perimeter in relation to rural municipalities which is located in the irrigated perimeter; and Ratio between the number of irrigators drinking water distributed by Deso and those who have access to it are presented as the main obstacles in the path towards sustainability of the activities that depend on the uses of the dam s waters.